Nonparticipation in work and education in emerging adulthood and depressive symptoms through early midlife - Michael Caniglia (SSM - Mental Health)
More than one-in-eight young adults in the US between the ages of 16–24 were not in employment, education, or training (NEET) in 2020 – a level not seen since the Great Recession. This study examines the long-term association between NEET status in emerging adulthood and later depressive symptoms using the National Longitudinal Study of Adolescent to Adult Health (1995–2018). Growth curve models chart the association between NEET status and depressive symptoms over time in the US. The analytic sample includes 9349 individuals and 28,047 person-wave observations for respondents between ages 18 to 43. In a fully specified model, respondents who reported NEET status in emerging adulthood (ages 18–26), exhibited greater depressive symptoms across emerging adulthood through early midlife (ages 33–43) (b = 0.44, 95% CI 0.33, 0.54) compared to those participating in employment, education, or training. Associations persisted even after accounting for early life disadvantage and using propensity score matching to further diminish possible sources of bias. Results indicate that disconnection from school and work during emerging adulthood may constitute a risk factor for depressive symptoms through early midlife.